Upaya Meningkatkan Pemahaman Murid Dengan Metode Role playing Materi Ketentuan Pernikahan Dalam Islam Kelas XI di SMKS Paramitha Bukittinggi - Deli Sinta; Sadrifal Sadrifal (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
This study aims to improve students' understanding of the material on Marriage Provisions in Islam through the application of the role-playing method in class XI at SMKS Paramitha Bukittinggi. The study used a Classroom Action Research (CAR) approach, which was carried out in two cycles, each cycle consisting of the planning, action, observation, and reflection stages. There were 32 students participating in this study. Data were collected through learning achievement tests, observation of teacher and student activities, and documentation. The results showed a significant increase in students' understanding. In cycle I, only 22% of students achieved learning completeness, while in cycle II, it increased to 84%. This shows that the role-playing method can create a more active, interactive, and enjoyable learning atmosphere, making it easier for students to understand the material in depth. Thus, the application of the role-playing method proved to be effective in improving student learning outcomes on the subject of Marriage Provisions in Islam.